Perkembangan Utang Luar Negeri Indonesia Tahun 2019 Sampai 2023 Berjalan - Widya Ratna Sari; Andriani; Faricha Lita Nabbila; Dewi Fatmala Putri (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose of writing is to determine the development of Indonesia's foreign debt from 2019 to 2023. The method applied in this research is a descriptive method with a qualitative descriptive research type, which utilizes a literature study approach. The data source used in this research is secondary data. Discussion Results: the development of Indonesia's foreign debt shows a fluctuating trend, with special attention in 2020 Indonesia's foreign debt increased, this was triggered by spending for handling the Covid-19 pandemic. Nevertheless, Indonesia's debt ratio is still within safe limits and the structure of Indonesia's foreign debt is still considered healthy, although several studies show that the relationship between the debt/GDP ratio is an early indicator of a bad economy. Therefore, joint synergy is needed in efforts to strengthen coordination between Bank Indonesia and the government sustainably to minimize risks that could affect economic stability.